Analisis Variasi Waktu Perendaman Deep Cryogenic Treatment dan Aging terhadap Pengujian Kekerasan pada Aluminium 6061 - Mahardika, Bimo Sakti; Naubnome, Viktor; Setiawan, Reza (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
Aluminum alloys are used more in industry due to its light weight, corrosion resistance, high strength, hardness, and recycling. This study examines the microstructure and hardness of 6061 aluminum alloy treated with Deep Cryogenic Treatment for 2, 12, 24, and 48 hours, followed by 1 hour of 1500C aging. Vickers hardness and microstructure testing will occur. The test results show that the hardness value has increased compared to the raw material. In the raw material variation, the hardness value is 53.4 HVN. The 2-hour immersion time variation experienced an increase in hardness value of 48.59% compared to the raw material. In the 12-hour soaking time variation, there was an increase of 43.9%. While the 24-hour and 48-hour variations also experienced an increase of 21.76% and 28.52% compared to the raw material. This is influenced by the microstructure that changes along with the variation in soaking time. Precipitates form due to the influence of deep cryogenic treatment which results in the hardness value of the 24-hour and 48-hour time variations decreasing compared to the 2-hour and 12-hour time variations.